Relationships after TBI: A grounded research study. (April 2014) - Godwin, Emilie; Chappell, Brittney; Kreutzer, Jeffrey
Abstract Background: While study on the emotional effects of traumatic brain injury (TBI) for individuals and caregivers has increased dramatically over the years, insufficient research has been performed on TBI's impact on the coupled relationship or the healing process successful couples go through following injury. As such, couples are left on their own to adjust to the complex challenges that TBI brings. Methods: This qualitative study aims to develop a framework for conceptualizing and assessing couples after TBI. Additionally, it purposes to establish a foundation built upon the practises of successful couples that have subsisted TBI from which methods of treatment can be drawn. Existing personal narratives written by survivors of TBI and their caregivers were analysed. Data triangulation with clinician-authored literature was performed. Constant comparative analysis of the data was then performed through an involving substantive and theoretical coding. Results: Five primary themes emerged: Ambiguous Losses, Identity Reformations, Tenuous Stability, Non Omnes Moriar and The New Us. From these, two grounded theories were developed: Relational Coring and Relational Recycling. Conclusions: These theories will allow researchers and practitioners to grasp the impact of TBI on the coupled relationship, familiarize themselves with the process by which relational experiences following TBI interact and understand the ways in which couples respond to these interacting experiences to work toward relational healing.